Chiral Auxiliaries for Stereoselective Electrophilic Aromatic Substitutions - Sharafi, Mona; Campbell, Joseph P.; Murphy, Kyle E.; Osadchey Brown, Reilly; Schneebeli, Severin T. (Synlett, 2020)
Electrophilic aromatic substitution reactions are of profound importance for the synthesis of biologically active compounds and other advanced materials. They represent an important means to activate specific aromatic C–H bonds without requiring transition-metal catalysts. Surprisingly, few stereoselective variants are known for electrophilic aromatic substitutions, which limits the utility of these classical reactions for stereoselective synthesis. While many electrophilic aromatic substitutions lead to achiral products (due to the planar nature of aromatic rings), there are important examples where chiral products are produced, including desymmetrization reactions of aromatic cyclophanes and of prochiral substrates with multiple aromatic rings. This Synpacts article now illustrates how chiral arms, when placed precisely above and underneath delocalized carbocations, can act as chiral auxiliaries to convert classical electrophilic aromatic substitution reactions into powerful diastereo- and enantioselective transformations.
Keywords: electrophilic aromatic substitution; enantioselective transformation; chiral auxiliary; density functional theory; Wheland intermediate; polyaromatics; chirality-assisted synthesis; through-space reaction control